General reviews. (1st April 2016) - Stoneman, Rod; Johnson, Veronica; Goss, Brian Michael
Design by Ikea, Sara Kristoffersson (2014) London: Bloomsbury, 148 pp., ISBN: 9780857858146, p/bk, £19.98The Black Irish Onscreen: Representing Black and Mixedrace Identities on Irish Film and Television, Zelie Asava (2013) Bern: Peter Lang, 213 pp., ISBN: 3034308396, p/bk, £36.00The Cinema of Michael Winterbottom: Borders, Intimacy, Terror, Bruce Bennett (2014) 1st ed., London: Wallflower Press, 232 pp., ISBN: 9780231167376, p/bk, £18.50; ISBN: 9780231167369, h/bk, £33.50